Key Technical Contents of the China VI Emission Standards for Diesel Fuelled Heavy-Duty Vehicles. Issue 1 (1st January 2019) - Gang, Li; Ying, Yuan; Minghui, Zhang; Xin, Zhao; Liang, Ji
The publication and implementation of the China VI emission standards for diesel fuelled heavy-duty vehicles is one of the important measures to fulfil the 'blue sky defence' action plan in China. This paper, by interpreting the background and key technical contents of the China VI emission standards, analyses the basis of the technical requirements and their impact. Moreover, it demonstrates the main differences between the China VI and China V emission standards and the Euro VI regulations, hoping to give the relevant industry in-depth insights into the new standard.